The Impact of Harmonious Culture and Entrepreneurship Training on Loan Repayment Performance at Microfinance in Indonesia - I Putu Astawa (APMBA (Asia Pacific Management and Business Application), 2018)
Studies on topic such as loan repayment at microfinance institutions are increasingly interesting due to the slumped current global economic condition and the many occurrences of bad debts. Various ways found by the researchers to increase loan repayment. Those ways are, for example, monitoring, mentoring, training, and economic approach. The research is different to previous research in terms of approach used, which is by linking harmonious culture to the loan repayment rate. The research aims to analyze the relationship between entrepreneurship training and harmonious culture in the effort to increase loan repayment of companies (debtors). 358 qualified debtors are used in the research. Data on the loan repayment rate in 2012 is used as a base for evaluation and reevaluated in 2017 in the same sample. In addition, an assessment on the perception of debtors toward the entrepreneurship training and the implementation of harmonious culture by microfinance institutions is conducted through questionnaire distribution. Data collected is analyzed using regression analysis. The result of regression analysis indicates that entrepreneurship training in form of the ability to develop business, entrepreneurship skill, and marketing skill has no relationship with loan repayment rate. Assistance program in form of cost in increasing faith to God through ceremonies at the companies give new spirit to achieve optimism in business progress since debtors believe that there are other forces in addition to human efforts that could change the business achievement. Cultural activities in maintaining harmonious relationship with others and natural environment gives positive impact on the increase in loan repayment. Harmonious culture implemented by the debtors linked to business activities in form of loan repayment is something new. The research result gives suggestion on human capital theory that harmonious culture is an attribute in determining one’s performance.